Radical classes of l-groups - Dao-Rong Ton (International Journal of Mathematics and Mathematical Sciences)
The main results of this paper concern radical classes of l-groups. In the sections 2-3 the relationship between several radical classes of l-groups are discussed and the characteristic properties for several radical mappings are given. In the sections 5-6 we give nice concrete descriptions of some important radical classes of l-groups using the structure theorems of a complete l-group and an Archimedean l-group.